Effect of Modeling Resins on Microhardness of Resin Composites - KORKUT, BORA; TARÇIN, BİLGE; TÜRKMEN, CAFER; YILMAZ ATALI, PINAR (My University, 2021)
Abstract Objectives This study was aimed to determine the effects of modeling resins on the surface microhardness of composites. Materials and Methods Six resin-based composites (Charisma Smart, Estellite Asteria, CeramX-One SphereTEC, Admira Fusion, Filtek Ultimate, and Clearfil Majesty Es-2) and three wetting agents (Modeling Liquid, Composite Primer, and Modeling Resin) were investigated. In all, 240 specimens were prepared, and wetting agents were applied prior to light curing in the experimental groups. After 24 hours, specimens were polished and Vickers microhardness (VHN) values were measured. Statistical Analysis Shapiro–Wilk and two-way analysis of variance (ANOVA) were used for analyses (p < 0.05). Results Both modeling resin and composites were determined to be effective factors (p < 0.001). The control group showed the highest VHN (70.37 ± 7.94), followed by Modeling Liquid (64.68 ± 12.07), Composite Primer (59.84 ± 6.33), and Modeling Resin (58 ± 3.52b; p < 0.001). Filtek Ultimate showed the highest VHN (76.62 ± 9.78c), whereas Charisma Smart (58.87 ± 7.95), and Clearfil Majesty (67.27 ± 2.58) showed the lowest (p < 0.001). Clearfil Majesty–Modeling Liquid (46.62 ± 5.33) and Charisma Smart–Composite Primer (50.81 ± 0.39) combinations showed the lowest VHN, whereas Filtek Ultimate–control (87.15 ± 2.12) and Filtek Ultimate–Modeling Liquid (84.24 ± 3.11) showed the highest (p < 0.001). Conclusion All tested modeling resins decreased VHN value, and the amount of reduction varied among composites and wetting agents. It might be safer not to use wetting agents unless they are necessary.